The Relationship Between Sleep Quality and Acne Severity (Acne Vulgaris) in Medical Students of Prima Indonesia University, Class of 2022 - Jeremi Cornellius Surbakti; Herlin Novita Pane; Muhammad Chairul (Jurnal Ners, 2025)
Acne vulgaris is one of the most common skin diseases worldwide with a global prevalence of 9.38% for all age groups, particularly affecting medical students who experience high academic stress and irregular sleep patterns. Despite numerous studies investigating the relationship between sleep quality and acne vulgaris, research findings show significant inconsistencies. This study aimed to identify the relationship between sleep quality and acne vulgaris severity among medical students at Prima Indonesia University batch 2022. A cross-sectional analytical observational study was conducted using quantitative methods. The population consisted of all medical students from batch 2022 (199 students) with a sample of 67 respondents determined using the Slovin formula with 90% confidence level. Simple random sampling technique was applied with inclusion criteria of students with acne vulgaris who were willing to participate. Data collection used validated instruments: Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality and Global Acne Grading System (GAGS) to assess acne severity. Data analysis was performed using SPSS version 29 with univariate and bivariate analysis using Chi-square test. Results showed that 70.1% of respondents had good sleep quality and 92.5% had mild acne severity. The Chi-square test revealed no significant relationship between sleep quality and acne vulgaris severity (p-value = 0.994, p > 0.05). This study concludes that sleep quality does not significantly affect acne vulgaris severity in medical students, suggesting that multifactorial approaches focusing on stress management, dietary patterns, skin hygiene, and cosmetic use may be more effective for acne management.